Humans. Season 3.0 [videorecording (DVD)] - Berrington, Emily; Bonnar, Mark; Bradley, Ruth, 1987- (Acorn Media, 2019)
As the hit sci-fi drama returns, one year has passed since the synths began to gain consciousness. Fighting to survive in a world that hates and fears them, the synth community starts to fracture, risking all hope for peace and stability with humans.